Optimization of Sports Performance: Analysis of the use of ergogenic nutritional aids by elite athletes representing Peru at an international level - Gonzales-Krapp, Vannia (2024)
In this cross-sectional descriptive study, the relationship between knowledge and consumption of ergogenic nutritional aids was evaluated in Peruvian athletes featured in the Lima 2019 Pan American Games. A total of 238 athletes from the Peruvian Sports Institute were surveyed using a questionnaire of 23 interrogations. The results revealed a high level of knowledge, with 99.6% of respondents familiar with ergogenic nutritional aids, and 93.7% admitting their use. The main motivation for consumption was guidance from nutritionists (38.1%), followed by recommendations from trainers (24.2%). A significant and positive relationship was identified between knowledge and consumption of ergogenic nutritional aids. A disparity in consumption was observed between genders, with men having a higher average intake and knowledge compared to women. Likewise, it was highlighted that with age both consumption and knowledge of these ergogenic nutritional aids increased. This analysis provides valuable insight into the dynamics of the use of ergogenic nutritional aids in high-performance athletes in the Peruvian context, highlighting the influence of health professionals and coaches on consumption decisions.